Nonrigid registration of 2-D and 3-D dynamic cell nuclei images for improved classification of subcellular particle motion - Kim, Il-Han; Chen, Yi-Chun M.; Spector, David L.; Eils, Roland; Rohr, Karl (IEEE transactions on image processing, 2011)
The observed motion of subcellular particles in fluorescence microscopy image sequences of live cells is generally a superposition of the motion and deformation of the cell and the motion of the particles. Decoupling the two types of movements to enable accurate classification of the particle motion requires the application of registration algorithms. We have developed an intensity-based approach for nonrigid registration of multichannel microscopy image sequences of cell nuclei. First, based on 3-D synthetic images we demonstrate that cell nucleus deformations change the observed motion types of particles and that our approach allows to recover the original motion. Second, we have successfully applied our approach to register 2-D and 3-D real microscopy image sequences. A quantitative experimental comparison with previous approaches for nonrigid registration of cell microscopy has also been performed.